1975
DOI: 10.1111/j.0954-6820.1975.tb04902.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Effect of Atrial Triggered Versus Fixed Rate Pacing at Rest and During Exercise in Complete Heart Block

Abstract: The central haemodynamics at rest and during exercise have been studied in 25 patients with complete AV block who were treated with fixed rate (FRP) and atrial triggered pacemakers (ATP). The aim of the investigation has been to study the effect of a synchronized atrial contraction for the filling of the ventricles and for the cardiac output (Q̇). Pressures and Q̇ have been determined during heart catheterization. The P wave for triggering the atrial synchronized pacemaker has been obtained with an electrode i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They instituted atrial synchronous ventricular pacing by recording the atrial P waves from an electrode that was positioned behind the atria via mediastinoscopy to trigger the ventricular stimulation rate of the pacemaker. This pioneering work was well summarized by Karlöf who showed that this pacing modality was superior to the prevailing fixed‐rate ventricular stimulation. Other lines of research investigated the possibility of detecting pacemaker failures before they became clinically apparent.…”
Section: Endurance Exercise and The Heartmentioning
confidence: 99%
“…They instituted atrial synchronous ventricular pacing by recording the atrial P waves from an electrode that was positioned behind the atria via mediastinoscopy to trigger the ventricular stimulation rate of the pacemaker. This pioneering work was well summarized by Karlöf who showed that this pacing modality was superior to the prevailing fixed‐rate ventricular stimulation. Other lines of research investigated the possibility of detecting pacemaker failures before they became clinically apparent.…”
Section: Endurance Exercise and The Heartmentioning
confidence: 99%